Aesthetics and the Limits of the Extended Mind. (23rd January 2019) - Nannicelli, Ted
Abstract: This paper seeks to establish closer connections and spur dialogue between philosophers working on 4E cognition and aestheticians. In part, the aim is to offer a critical overview of the ways 4E research might inform our understandings of the arts. Yet it is also partly to flag some potential art-specific challenges to some of the theses found within the 4E literature. I start by examining the strongest extant claims regarding art (specifically music) and active externalism, and argue that it is hard to see either how active externalism could square with our actual appreciative practices or that its explanatory value could be sufficient to pressure us to revise radically those practices. Furthermore, I argue, rejecting active externalism seems necessary to acknowledge adequately the important ways in which artistic creation often involves the application of embodied know-how or the execution of embodied skills. For this reason, I argue, embodied approaches to cognition are better positioned to complement and inform the humanistic methods traditionally employed in philosophical aesthetics and art theory. (So, too, I argue, are embedded approaches to cognition, which emphasize the use of artefacts and elements of our surrounding environment as scaffolds for cognition.) However, I conclude on a moderately sceptical note: the challenge still outstanding for these approaches is to yield new understandings of our artistic practices that have not been (and could not be) gleaned through traditional humanistic inquiry.